2006
DOI: 10.1002/jcb.21010
|View full text |Cite
|
Sign up to set email alerts
|

Calcium‐pH Crosstalks in the human mast cell line HMC‐1: Intracellular alkalinization activates calcium extrusion through the plasma membrane Ca2+‐ATPase

Abstract: The human mast cell line (HMC-1) has been used to study the relationship between intracellular pH and cytosolic calcium (Ca2+) in mast cells. Thapsigargin (TG) caused store-operated Ca2+ entry, that is enhanced by the PKC activator PMA. NH4Cl-induced alkalinization showed an inhibitory effect on TG-sensitive stores depletion (not on TG-insensitive stores), and also on final cytosolic Ca2+ levels reached in response to both TG and the ionophore ionomycin. Loperamide, a positive modulator of store-operated chann… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
7
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 51 publications
2
7
0
Order By: Relevance
“…PMA alone does not induce exocytosis in RBL‐2H3 cells, in opposition to what is observed in serosal rat mast cells [Beaven et al, 1987; Wolfe et al, 1996]. In a previous work we have found that activation of PKC with PMA alone does not activate histamine release in HMC‐1 cells [Pernas‐Sueiras et al, 2005a]. In mast cells, PKC plays a primordial role on degranulation, since it has been reported to increase exocytosis elicited by stimuli such as thapsigargin (TG) or Ca 2+ ionophores.…”
mentioning
confidence: 75%
See 1 more Smart Citation
“…PMA alone does not induce exocytosis in RBL‐2H3 cells, in opposition to what is observed in serosal rat mast cells [Beaven et al, 1987; Wolfe et al, 1996]. In a previous work we have found that activation of PKC with PMA alone does not activate histamine release in HMC‐1 cells [Pernas‐Sueiras et al, 2005a]. In mast cells, PKC plays a primordial role on degranulation, since it has been reported to increase exocytosis elicited by stimuli such as thapsigargin (TG) or Ca 2+ ionophores.…”
mentioning
confidence: 75%
“…We have demonstrated that exocytosis can be triggered in this cellular model with just an intracellular alkalinization and no Ca 2+ increase [Pernas‐Sueiras et al, 2005b]. We have also reported that the NH 4 Cl‐induced intracellular alkalinization negatively modulates cytosolic Ca 2+ levels, probably by activation of Ca 2+ efflux through the plasma membrane Ca 2+ /H + ‐ATPase [Pernas‐Sueiras et al, 2005a]. In the present study, we explore how different kinase pathways modulate histamine release elicited by two well‐known stimuli such as the Ca 2+ ‐ionophore ionomycin and NH 4 Cl, two drugs that we have used for our previous works, and that have also been reported to release histamine in different cellular models [Hsu and MacGlashan, 1996; Teofoli et al, 1999; Alfonso et al, 2005; Pernas‐Sueiras et al, 2005b].…”
mentioning
confidence: 89%
“…Following to our previous work in HMC‐1 560 cells [Pernas‐Sueiras et al, 2005, 2006a,b], we checked the effect of TyrK inhibitors on histamine release induced by alkalinisation and ionomycin.…”
Section: Resultsmentioning
confidence: 99%
“…Cytosolic Ca 2+ concentrations play a role in exocytotic processes since the Ca 2+ ionophore ionomycin induces histamine release by modulating intracellular Ca 2+ concentration [Pernas‐Sueiras et al, 2005, 2006b]. Therefore, similar experiments using ionomycin instead of NH 4 Cl were performed.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in HMC‐1 have clearly demonstrated that they also show this behaviour after alkalinisation. Exocytotic process takes place without affecting intracellular Ca 2+ concentrations [Pernas‐Sueiras et al, 2005, 2006a,b]. In those studies, we used HMC‐1 560 cells that carry a mutation in the proto‐oncogene c‐kit that leads to a Glycin → Valin amino acid exchange in position 560 of the receptor TyrK KIT.…”
Section: Discussionmentioning
confidence: 99%